Interlingual subtitling of nonsensical words, phrases and utterances in the movie Alice in Wonderland / Nur Syuhada Farhana A Zahari - Nur Syuhada Farhana , A Zahari (2017)
Alice in Wonderland has always held a prevailing repute on its whimsical storyline and surreal characters for more than a century and a half (Craig, 2015). Its prominent language style has altered linguistic conventions through nonsensical utterances, puns and portmanteau. Its substantially unique language has led to a significant concern on the interlingual subtitling through its film adaptation by Tim Burton (2010). The purpose of this study is to explore the interlingual subtitling strategies employed in translating nonsensical words, phrases and utterances in Malay subtitles from the movie Alice in Wonderland. Additionally, this study also seeks to investigate the effectiveness of the strategies applied in translating the selected nonsensical words, phrases and utterances. Data for this study were obtained through the transcription of the movie subtitles and analysed using a descriptive qualitative approach. On the basis of the results of this research, it can be concluded that ‘Imitation’, ‘Transfer’, ‘Transcription’ and ‘Paraphrase/ Translation by cultural substitution’ respectively are the most frequent strategies used in translating the nonsensical words, phrases and utterances. However the results also reveal that the available framework for types of subtitling strategies are not relatively applicable to analyse nonsensical words, phrases and utterances and such framework should be enhanced to incorporate the qualities of nonsensical language. In spite of this, there are seven (7) combined strategies discovered throughout the analysis as a result of the nonsensical words, phrases and utterances that partially partook more than one strategy. Consequently, these results support the view that the visual illustration has aided the effectiveness of the subtitles in complementing the nonsensical words, phrases and utterances. All in all, the findings of this study will help to confirm and refine the criteria for subtitling of nonsensical language while aiding the scholars of translation and practitioners to understand the range of important considerations that need to be made when undertaking future translation/subtitling tasks for nonsensical language.